Per-Service music teacher education in Germany and Austria: A perspectiva from central Europe - Rodríguez- Quiles y García, José A. (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
After the Declaration of Bologna in 1999, it is worthy to have a look at the interpretations that different countries have made in order to achieve a common European Higher Education Area (EHEA), in particular in the field of music teacher education. As two significant examples of Central Europe, the new situation in Germany and Austria are analysed in this paper in order to find out about how Beethoven’s and Mozart’s countries have improved their educational systems once these changes have been implemented in some of their institutions of higher education